Gold and nickel alkyl substituted bis-thiophenedithiolene complexes: anionic and neutral forms. Issue 2 (15th December 2016) - Andrade, Marta M.; Silva, Rafaela A. L.; Santos, Isabel C.; Lopes, Elsa B.; Rabaça, Sandra; Pereira, Laura C. J.; Coutinho, Joana T.; Telo, João P.; Rovira, Concepció; Almeida, Manuel; Belo, Dulce
Abstract : The effect of substituents on the magnetic and transport properties is assessed for Au and Ni alkyl substituted bisthiophenedithiolates. Abstract : The Au and Ni monoanionic complexes of tert -butyl and diisopropyl substituted thiophenedithiolate ligands, [M(α- tb -tpdt)2 ] and [M(α- dp -tpdt)2 ], were synthesized and characterized namely by single crystal X-ray diffraction and magnetic susceptibility measurements. These complexes, prepared in a first step as monoanionic species, are easier to oxidize than the related non-substituted thiophenedithiolates and could be obtained also as stable neutral species. As expected, the peripheral alkyl groups in the ligands also confer a high solubility to the complexes in common organic solvents. The neutral gold complex [Au(α- tb -tpdt)2 ] presents a significant ligand asymmetry indicative of unpaired electron localization in one ligand at variance with [Au(α- dp -tpdt)2 ] that is within experimental uncertainty fully symmetric illustrating the role of intermolecular interactions in the stabilization of SOMO⋯SOMO interactions. While in [Au(α- tb -tpdt)2 ] a significant intermolecular interaction between paramagnetic molecules is possible leading to diamagnetic dimers of molecules, in [Au(α- dp -tpdt)2 ] the bulkier substituents prevent the intermolecular interactions, leading to a regular stacking of molecules in symmetrical configuration. The regular stacks of paramagnetic [Au(α- dp -tpdt)2 ] units behave, at high temperatures, as antiferromagnetic chains undergoing an AFM transition at ca. 25 K.